Stopping performance flight test on a flooded runway - Tump, R.S.; Mulder, T.J. (Society of Experimental Test Pilots, 2017)
One of the identified solutions for runway excursions is the research into the “Impact of fluid contaminants of varying depth on aircraft stopping performance”. For this, NLR has carried out water-pond flight testing with the NLR/TUD Cessna Citation research aircraft to assess braking performance of modern aircraft and tyres on water covered runways. Airbus Military performed the same test using an A400M. Both tests took place using the water-pond facility of NLR. Aircraft operating on runways that are contaminated by standing water or slush (> 3 mm, up to the AFM limit) are significantly affected in take-off and landing performance. Most data available today is bases on test carried out in the 60s and 70s of the last century. Improved aircraft braking systems and tires were only tested at small scale in recent years.
Keywords: Flight safety